Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

Sure, you can try

So I would first start by multiplying both sides by two-
A(2) = (b + c) h

Sure

then I would subtract c from both sides-
a(2) - c

a(2) - c = b(h)

yeah, no. that doesnt work.

but aren't we trying to figure out the formula for h?

Exactly! So a(2) - (b+c) = h
correct?

\[\sf 2A=(b+c)h\]\[\sf h=\frac{2A}{b+c}\]

Thank you guys